Pengaruh Strategi Pembelajaran Berorientasi Aktivitas Siswa Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas X SMK Negeri 1 Sigumpar Tahun Pembelajaran 2022/2023 - Tri Women Hasibuan; Dame Taruli Simamora; Wilson Simanjuntak (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2023)
The aim of this research is to find out how student’s activity-oriented learning strategies influence the learning outcomes of Christian Religious Education And Character Education for class. The method used in this research is a quantitative research method with inferential descriptive data analysis. The population is all class data was collected questionnaire with 30 item for variable X. 1) Test the analysis requirements: a) positive relationship obtained rxy = 0.552>rtable (a=0.05, n=52)=0.297. b) Testing a significant relationship obtained tcount= 4,683>ttable= (a=0.05, dk=n-2=50)= 2.000. 2) influence test: a) regression equation test, obtained regression equation Y=69.36+0,14 X. b) regression coefficient of determination test (r2)= 30.5%. 3) test the hypothesis using the F test to obtain Fcount>Ftable= (a=0.05, dk= numerator k = 16, dk denominator= n-2=52-2=50) namely 21,85>1,39. Thus Ha is accepted and H0 is rejected.